Silanization of Silica Nanoparticles and Their Processing as Nanostructured Micro-Raspberry Powders—A Route to Control the Mechanical Properties of Isoprene Rubber Composites - Stauch, Claudia; Ballweg, Thomas; Haas, Karl-Heinz; Jaeger, Raimund; Stiller, Stefan; Shmeliov, Aleksey; Nicolosi, Valeria; Malebennur, Sriharish; Woetzel, Jacqueline; Beiner, Mario; Luxenhofer, Robert; Mandel, Karl (Polymer Composites, 2019)
Depending on interparticle structure and chemical behavior, fillers greatly influence the mechanical properties in rubber compounds. In this work, the influence of the filler–matrix versus filler–filler interaction on the mechanical properties of a silica nanoparticle–rubber composite was investigated. For this purpose, nanostructured microraspberry particles with different surface properties were designed and prepared using colloidal silica and two different kinds of silane agents, one coating agent (triethoxyoctylsilane, OCTEO) and one coupling agent (bis(triethoxysilylpropyl)tetrasulfide, Si69™). In addition, the degree of silane coverage of the nanoparticles was adjusted in a precisely controlled way. This sophisticated particle system allowed for straightforward integration into the composite formation process while ensuring that a redispersion of the nanoparticles in the rubber matrix occurred during compounding. With this microraspberry particle system, it was possible to influence the mechanical properties by the degree of silane surface coverage on the nanoparticles while the filler content could be kept constant. The two silane systems were carefully compared and the impact of the particle/particle and the particle/rubber interactions with respect to the mechanical properties of the composite was studied. Ultimately, an overall picture of the influence of the type and the amount of silane on mechanical properties in silica–rubber composites could be obtained. POLYM. COMPOS., 40:E732–E743, 2019. © 2018 Society of Plastics Engineers.
CRIS-Team Scopus Importer:2020-04-02